ANALISIS PERILAKU KONSUMEN GEN Z DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN ONLINE DI ERA DIGITAL (STUDI PADA KONSUMEN DI KOTA PADANG) - Nurhayati, Nurhayati (Bajang Institute, 2025)
This study aims to analyze the purchasing behavior of Generation Z in making online buying decisions in the digital era, focusing on five key variables: platform usability, trust in the platform, the influence of social media and influencers, price and promotional perceptions, and consumer reviews. The research employed a quantitative approach using a survey method with 50 Gen Z respondents in Padang City. Data were analyzed using multiple linear regression to measure the influence of each variable on purchasing decisions. The results indicate that all respondents are active e-commerce users, whose purchasing behavior is shaped not only by rational considerations but also by emotional moments such as flash sales on double-date promotions, live shopping features, and the use of pay-later payment methods. Platform usability emerged as the most dominant factor, contributing 32%, followed by trust (26%), social media influence (18%), price and promotion (12%), and consumer reviews (12%). The regression model yielded an R² value of 0.730 with a significance level of < 0.05, indicating that the five variables collectively explain 73% of the variance in Gen Z’s online purchasing decisions. The study concludes that Gen Z consumer behavior is multifactorial, where purchasing decisions are influenced not only by technical aspects but also by interactive digital experiences and social dynamics. These findings suggest the need for digital marketing strategies that integrate emotional, social, and visual elements to effectively engage Gen Z consumers.